Kinetic Monte Carlo Modeling of the Spontaneous Deposition of Platinum on Au(111) Surfaces - María Cecilia Gimenez; Oscar A. Oviedo; Ezequiel P. M. Leiva (Entropy, 2025)
The spontaneous deposition of platinum (<semantics>Pt</semantics>) atoms on <semantics>Au(111)</semantics> surfaces is systematically investigated through kinetic Monte Carlo simulations within the Embedded Atom Model framework. The kinetic model aims to capture both stoichiometric, atomic-scale interactions and the more relevant processes that describe the kinetics of a physical problem. Various deposition rates are examined, encompassing a thorough exploration of <semantics>Pt</semantics> adsorption up to a coverage degree of <semantics>θ=0.25</semantics>. The resulting 2D islands exhibit a ramified structure, mirroring the experimental methodologies. For the first time, this study extensively analyzes the dependence of both the mean island size and island density on spontaneous deposition, thereby offering valuable insights into the intricate dynamics of the system.